Evaluación del servicio de recolección de desechos sólidos que brinda la dirección de Gestión Ambiental del Gobierno Autónomo Descentralizado cantón Chone - Loor Vélez, Quinche Monserrate (2022)
The general objective of the investigative work was the evaluation of the solid waste collection service provided by the Environmental Management Directorate of the Decentralized Autonomous Government in Chone Canton. The applied methodology was the inductive, deductive and analytical method. Bibliographic, field and descriptive research was used, which facilitated the development and execution of the investigation. Different epigraphs that are the bibliographic support of the operative part of the work were highlighted. Likewise, techniques such as observation, interview and survey were used to obtain relevant data and information on the solid waste collection service. It was identified that 52% of the urban population is unaware of the services provided by the Department of Environmental Management of the GAD, as well as that 85% of the people in the city are not aware of solid waste and how it affects human life and environmental degradation. In such a way, that there is the presence of dissatisfaction and nonconformity for the services offered by the municipality, for which an improvement plan is proposed as an ideal proposal for the fulfillment of institutional goals and objectives and the improvement of services of solid waste collection provided to citizens